The Influence of Facilities and Prices on Interest in Returning to West Java International Airport (BIJB) - Hidayat, Kharis Pratama (PT. Global World Scientific, 2023)
This study aims to analyze the influence of facilities and prices on the intention to revisit West Java International Airport (BIJB) Kertajati. The background of this study is based on the low level of repeat visits by the public to BIJB, which is suspected to be caused by suboptimal facilities and the mismatch of price perceptions with the services received. This study uses a quantitative approach with multiple linear regression analysis methods on primary data obtained through questionnaires to airport service users. Two main hypotheses are tested in this study, namely the positive influence of facilities and prices on the intention to revisit, both partially and simultaneously. The results of the analysis show that both facilities and prices have a significant and positive influence on the intention to revisit BIJB Kertajati. The regression coefficients for facilities and prices are 0.228 and 1.772, respectively, indicating that price has a greater influence than facilities. This finding indicates that perceptions of affordability and suitability of price to benefits received are dominant factors in driving consumer loyalty. Therefore, BIJB managers need to improve the quality of facilities and establish competitive pricing strategies to attract service users sustainably.